Echocardiographic myocardial work in pre-adolescent male basketball players: a comparison with cardiopulmonary exercise test-derived aerobic capacity - Zhao, Kewei; Liu, Yu; Dong, Lili; Gao, Binghong (Frontiers in Physiology, 2022)
Background: Pressure-strain loop (PSL) analysis provides a novel, less load-dependent non-invasive method to quantify myocardial work and demonstrates a significant correlation with the contractile reserve in adult athletes. We aim to validate PSL-derived markers in characterizing LV function in pre-adolescent basketball players by comparing results before and after the cardiopulmonary exercise test (CPX) and explore its association with CPX-derived aerobic capacity. Methods: Cardiac morphology and function in 20 pre-adolescent basketball players were assessed at 9.7 years old (9.7±1.1years) before and after cardiopulmonary exercise testing. Echocardiography was performed in all subjects, including two-dimensional speckle-tracking echocardiography (STE). Simultaneous brachial-cuff-measured blood pressure was recorded to perform PSL analysis. Results: Nineteen subjects were included in the final analysis. Exercise training in pre-adolescent males was associated with lower global work index (GWI) and global work efficiency (GWE) at rest. GWE at stress was significantly correlated with VO2max and peak O2 pulse (P = .0122, r = 0.56; P = .00122, r = 0.69, respectively). When indexed by body mass, GWI and GWE both significantly correlated with relative VO2max (P = .0086 and .0011 respectively, r = 0.58 and 0.69 respectively); GWI and GWE at baseline and stress were all significantly correlated with peak O2 pulse (GWI at baseline, P < .0001, r = -0.90; GWE at baseline, P < .0001, r = -0.89; GWI at stress, P = .0289, r = -0.50; GWE at stress, P < .0001, r = -0.83). Conclusion: PSL-analysis-derived GWI and GWE at rest indexed by body mass are associated with cardiopulmonary exercise test-derived peak oxygen consumption and oxygen pulse in pre-adolescent athletes.